Liberia : Enhanced Initiative for Heavily Indebted Poor Countries Initiative; Request for Additional Interim Assistance; and Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper reviews the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC) Initiative for Liberia. Performance under the Extended Credit Facility (ECF)-supported program is solid. The third ECF review was completed on a lapse of time basis on December 18, 2009. All but one of the quantitative performance criteria (PC) for the end-June 2009 test date were observed. The PC on total revenue collection was not observed but the deviation was temporary and did not jeopardize program objectives. Structural reform commitments were largely met, though some with delays.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet